RAWVec – A Method for Watermarking Vector Maps - Marques, Douglas Aurélio; Magalhães, Karina M.; Dahab, Ricardo R. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2007: Anais do VII Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2007)
The information used in geographic information system (GIS) and in spatial data is represented by digital vector maps, which are expensive to produce, but easy to copy. Watermarks have been used for a long time in other digital media for both authentication and tracing. This work presents a new method for embedding watermarks, in the form of a bitmap image, into digital vector maps. The detection of the watermark is accomplished by extracting the embedded image and comparing it with the original one.